-5(-5u+6)-9u=4(u-7)-4

Simple and best practice solution for -5(-5u+6)-9u=4(u-7)-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(-5u+6)-9u=4(u-7)-4 equation:



-5(-5u+6)-9u=4(u-7)-4
We move all terms to the left:
-5(-5u+6)-9u-(4(u-7)-4)=0
We add all the numbers together, and all the variables
-9u-5(-5u+6)-(4(u-7)-4)=0
We multiply parentheses
-9u+25u-(4(u-7)-4)-30=0
We calculate terms in parentheses: -(4(u-7)-4), so:
4(u-7)-4
We multiply parentheses
4u-28-4
We add all the numbers together, and all the variables
4u-32
Back to the equation:
-(4u-32)
We add all the numbers together, and all the variables
16u-(4u-32)-30=0
We get rid of parentheses
16u-4u+32-30=0
We add all the numbers together, and all the variables
12u+2=0
We move all terms containing u to the left, all other terms to the right
12u=-2
u=-2/12
u=-1/6

See similar equations:

| x–5=4x+14 | | 175=(60-2x)(15-2x)(x) | | 4/9*x=10 | | -4h=-5h-8 | | 3/10=4/x | | .5h+.3333333333(h-6)=0.83333333333h+2 | | 2x-6=3x+1-x=7 | | 42=2f-6(2f+3) | | s+10=-s-10 | | -w²+5w-4=0 | | 2^n=625 | | 7k-10=k | | 3x+6(x-1)=12x+8-3x-14 | | 4(x-1)=5x+2-3(-3x-4) | | 2/3(x-3)-x=8 | | -2j=-j-8 | | y=1+1.3X | | 21+4y=-3 | | 4c=3c-8 | | 2.5+2.5+2x=2.5x | | 7(x-0.75)=2.8 | | 7g=-7+6g | | 8x+5+2x+5=180 | | 1/3(9-x6)=x | | 381.64=170+.74x | | −25x2+11=0 | | -6t-8-7=5+t | | -3=-8-2n | | 381.64=170x+.74 | | -10=2(2-7c) | | 3u-7+4(2u+2)=-3(u+5) | | 5x-4(x-3)=30 |

Equations solver categories